2021
DOI: 10.21037/apm-21-2080
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the benefits of different irradiation types on patients with postoperative locoregional recurrence of esophageal cell squamous carcinoma

Abstract: Background: To explore the benefits of different types of irradiation on patients with postoperative locoregional recurrence (LRR) of thoracic esophageal squamous cell carcinoma (ESCC).Methods: We analyzed the medical records of 344 patients with recurrent esophageal cancer (EC) at the Fourth Hospital of Hebei Medical University. All patients met an inclusion criteria that included having postoperative LRR (without distant metastasis), and having received either chemotherapy, radiotherapy, or chemoradiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Gao et al. ( 16 ) demonstrated that gender and synchronous chemotherapy were independent factors affecting patient prognosis (P=0.003, P<0.001). Lyu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al. ( 16 ) demonstrated that gender and synchronous chemotherapy were independent factors affecting patient prognosis (P=0.003, P<0.001). Lyu et al.…”
Section: Discussionmentioning
confidence: 99%